the THE RELATIONSHIP BETWEEN REPRODUCTIVE HEALTH EDUCATION AND CHANGES IN ADOLESCENTS KNOWLEDGE IN PREVENTING UNWANTED PREGNANCY AT SMP NEGERI 13 PEKANBARU: REPRODUCTIVE HEALTH EDUCATION - Brilian Dini Ma. Iballa; Bdn. Ade Febriani, SST., M. Kes Ade (LPPM Universitas Abdurrab, 2026)
Background: Unwanted pregnancy is a pregnancy that is not desired by the woman or her surroundings. This occurs due to various factors, making its presence unwanted by one or both prospective parents. Health education is an effort to create behaviors that support health. Objective: To determine the relationship between reproductive health education and changes in adolescents knowledge in preventing unwanted pregnancy at SMP Negeri 13 Pekanbaru. Methods: Quantitative research with a one group pretest-posttest design. The sample consisted of 70 respondents using a total sampling technique. Data were collected using questionnaires before and after education. Data were analyzed using the Wilcoxon test and Spearman correlation. Results: Before education, knowledge was good in 2 respondents (2.9%), fairly good in 14 respondents (20%), and poor in 54 respondents (77.1%). After education, knowledge was good in 57 respondents (81.4%), fairly good in 11 respondents (15.7%), and poor in 2 respondents (2.9%). The Wilcoxon test showed a p-value = 0.001 < 0.005, and the Spearman correlation test showed a p-value = 0.001 < 0.005, indicating changes in knowledge and a significant relationship. Conclusion: Reproductive health education increases adolescents’ knowledge in preventing unwanted pregnancy.